Low-threshold and multi-wavelength Q-switched random erbium-doped fiber laser. (5th February 2016) - Wang, Simin; Lin, Wei; Chen, Weicheng; Li, Can; Yang, Changsheng; Qiao, Tian; Yang, Zhongmin
Abstract: We demonstrate a low-threshold and multi-wavelength Q-switched random fiber laser with erbium-doped fiber as the gain medium and Rayleigh scattering as the randomly distributed feedback. Q-switched pulses are generated with threshold as low as 27 mW by combining random cavity resonances and the Q-value modulation effect induced by stimulated Brillouin scattering. The repetition rate is typically on the kilohertz scale with rms timing jitter of <5.5% and rms amplitude fluctuation of <30%. Raman Stokes emissions up to the third order are observed with an overall energy of nearly 42% of the pulse output, which may open an avenue for applications requiring multiple wavelengths.